Strategy of Idiom Translation from English to Indonesian: The Case of the Novel Rich People Problems - Efendi, Lutfi; Hardjanto, Tofan Dwi (English Department, Faculty of Humanities, Andalas University, 2023)
In idiom translation, strategies are employed to find equivalent results from the source language to the target language. There are challenges in translating idioms. The purpose of this study is to find idiom translation strategies in the novel Rich People Problems. In addition to idiom translation strategies, this article also aims to classify idioms in the novel. This study used a qualitative method and was supported by quantitative data using sampling technique. As a result, as Baker (2018) explaines, this article has three idiom translation strategies. They are (1) translation using paraphrase, (2) translation by the omission of a play, and (3) translation by the omission of the entire idiom. However, there are three strategies that are not used in this article. They are borrowing the source language idiom, using an idiom of similar meaning and form, and using an idiom of similar meaning but dissimilar form. Translation by paraphrasing is the most dominant strategy used to translate the idioms in this article, at a rate of 64.29%. In addition, this article also has the types of idioms proposed by Makkai (1972). These are (1) phrasal verb idioms, (2) tournure idioms, and the last (3) irreversible binomial idioms. Therefore, the main use of translating idioms by paraphrase may be due to time constraints for the translator due to the deadline for determining the idiom equivalences in the target language.